In, English Prepositions - Yulia Wahyuningsih (Universitas Muhammadiyah Lampung, 2021)
This research is a qualitative research which aims to describe the grammatical form of preposition in. This study uses Concordance to process Britain Awake's discourse in terms of Corpus Linguistics. This study shows that the preposition in can be in the form of simple prepositions and complex prepositions. These two forms of prepositions conform to the provisions put forward by experts, particularly the preposition formulas Preposition + Noun + Preposition. From the corpus data on oncordance, the simple prepositions is 73 (seventy three) and complex prepositions are 6 (six). The preposition in contains 13 (thirteen) of the 40 (forty) existing meanings.